(NH4)Bi2(IO3)2F5: An Unusual Ammonium‐Containing Metal Iodate Fluoride Showing Strong Second Harmonic Generation Response and Thermochromic Behavior. (9th January 2020) - Fan, Huixin; Lin, Chensheng; Chen, Kaichuang; Peng, Guang; Li, Bingxuan; Zhang, Ge; Long, Xifa; Ye, Ning
Abstract: An ammonium‐containing metal iodate fluoride compound, (NH4 )Bi2 (IO3 )2 F5, featuring a two‐dimensional double‐layered framework constructed by [BiO2 F5 ] 6− and [BiO4 F4 ] 9− polyhedra, as well as [IO3 ] − groups, was successfully synthesized. The well‐ordered alignment of these SHG‐active units leads to an extraordinary strong SHG response of 9.2 times that of KDP. Moreover, this compound possesses a large birefringence (Δ n =0.0690 at 589.3 nm), a wide energy band gap ( E g =3.88 eV), and a high laser damage threshold (LDT; 40.2×AgGaS2 ). In particular, thermochromic behavior was observed for the first time in this type of compound. Such multifunctional crystals will expand the application of nonlinear optical materials. Abstract : Multitalent : Die Einführung von Ammonium in ein Bismutiodatfluorid ergibt kristallines (NH4 )Bi2 (IO3 )2 F5, das eine feine Balance aus starker Obertonerzeugung, großer Doppelbrechung und hoher Laserschädigungsschwelle aufweist. Insbesondere wies der Kristall eine ungewöhnliche Thermochromie auf. Ein solches multifunktionelles Verhalten erweitert das Potential nichtlinear‐optischer Materialien (siehe Bild).